THE TECHNIQUES USED FOR THE TEACHING OF SPEAKING FOR YOUNG LEARNERS (RETAIN, 2013)
The main objective of learning English is using English as a means of communication. One of the ways for the teachers to make young learners use English as a means of communicationis using appropriate techniques which match with the learners’ characteristics in teaching speaking. Unfortunately, the fact shows that many teachers still do not know the appropriate techniques to teach speaking for young learners. They frequently teach speaking using translation and memorizing techniques, whereas, those techniques are not appropriate with the characteristics of young learners. In this case, the teachers have to know the applicable techniques for teaching speaking to young learners to achieve the main objective of teaching English. Thus, this paper will describe the successful techniques of teaching speaking for young learners employed by the teacher of Pre Beginner 1 level class’ learners at RAM English Course (REC).The teacher was a qualified teacher since she has understood about the applicable techniques for teaching speaking to young learners. This study is expectedto make the teachers at elementary schoolsable to apply the techniques in this study when teaching speaking to young learners in their class. A descriptive qualitative research was used to conduct this study andthe observation sheet and interview were the instruments to collect the data. The result showedthe techniques used by the teacher to teach speaking were information gap, repetition drill, picture narrating, and guessing games techniques. She frequently combined the techniques when teaching the young learners to avoid the boredom in the class. As the result, the learners had more chances to speak up with their friends since the class was not boring. They also had good ability of speaking and more motivated to learn English since the teacher used the appropriate techniques with their characteristics. Key words: Technique, teaching speaking, RAM English Course (REC).